Research into the psychological well-being of young refugees - Lau, Winnie (Int Psychiatry, 2008)
Interest in the psychological well-being of refugees and asylum seekers has steadily grown in recent years. Latest estimates indicate there are 32.9 million people of concern to the United Nations High Commissioner for Refugees (2006). A refugee is defined as being in that position because of a well-founded fear of persecution due to race, religion, nationality, social group or political opinion, and who is consequently outside and unable to return to his or her country. The status of ‘refugee’ is contrasted with that of a person seeking asylum, whose experiences may be similar but who is not formally determined in the same way.